Effects of a COVID-19 Public Health Lockdown on Drinking and Health Behavior Among Persons with HIV and with Unhealthy Alcohol use in Uganda - Beesiga, Brian; Marson, Kara; Fatch, Robin; Emenyonu, Nneka I.; Adong, Julian; Kekibiina, Allen; Puryear, Sarah; Lodi, Sara; McDonell, Michael G.; Muyindike, Winnie R.; Kamya, Moses R.; Hahn, Judith A.; et al. (AIDS and Behavior, 2023)
To better understand the impact of Uganda’s initial COVID-19 lockdown on alcohol use, we conducted a cross-sectional survey (August 2020-September 2021) among persons with HIV (PWH) with unhealthy alcohol use (but not receiving an alcohol intervention), enrolled in a trial of incentives to reduce alcohol use and improve isoniazid preventive therapy. We examined associations between bar-based drinking and decreased alcohol use, and decreased alcohol use and health outcomes (antiretroviral therapy [ART] access, ART adherence, missed clinic visits, psychological stress and intimate partner violence), during lockdown. Of 178 adults surveyed whose data was analyzed, (67% male, median age: 40), 82% reported bar-based drinking at trial enrollment; 76% reported decreased alcohol use during lockdown. In a multivariate analysis, bar-based drinking was not associated with greater decreases in alcohol use during lockdown compared to non-bar-based drinking (OR = 0.81, 95% CI: 0.31–2.11), adjusting for age and sex. There was a significant association between decreased alcohol use and increased stress during lockdown (adjusted β = 2.09, 95% CI: 1.07–3.11, P < 0.010), but not other health outcomes.
Keywords: Coronavirus disease-19 (COVID-19); HIV; TB; Lockdown; Unhealthy alcohol use